2014
DOI: 10.1021/es504157v
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic Resistance Genes and Bacterial Pathogens in Long-Term Manured Greenhouse Soils As Revealed by Metagenomic Survey

Abstract: Antibiotic resistance genes (ARGs), human pathogenic bacteria (HPB), and HPB carrying ARGs pose a high risk to soil ecology and public health. Here, we used a metagenomic approach to investigate their diversity and abundance in chicken manures and greenhouse soils collected from Guli, Pulangke, and Hushu vegetable bases with different greenhouse planting years in Nanjing, Eastern China. There was a positive correlation between the levels of antibiotics, ARGs, HPB, and HPB carrying ARGs in manures and greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(113 citation statements)
references
References 34 publications
5
106
1
1
Order By: Relevance
“…Previous studies have suggested that dominant human pathogens in manure were Bacillus anthracis and Bordetella pertussis (Fang et al, 2015), and those in sewage sludge were Escherichia coli and Klebsiella pneumoniae (Ye and Zhang, 2011), however, we did not detect these in our samples. One reasonable explanation is that these pathogens detected in sewage sludge or manures could not successfully establish in the present soil.…”
Section: Responses Of Bacterial Pathogenscontrasting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have suggested that dominant human pathogens in manure were Bacillus anthracis and Bordetella pertussis (Fang et al, 2015), and those in sewage sludge were Escherichia coli and Klebsiella pneumoniae (Ye and Zhang, 2011), however, we did not detect these in our samples. One reasonable explanation is that these pathogens detected in sewage sludge or manures could not successfully establish in the present soil.…”
Section: Responses Of Bacterial Pathogenscontrasting
confidence: 93%
“…One reasonable explanation is that these pathogens detected in sewage sludge or manures could not successfully establish in the present soil. This hypothesis is supported by a recent study, in which, it was reported that although Bacillus anthracis and Bordetella pertussis were detected in manure, they were not detected in manure-amended soil (Fang et al, 2015). In this study, the identification of bacterial pathogens was based on the use of the 16S rRNA gene sequence from each sample blast against the bacterial pathogen 16S rRNA database.…”
Section: Responses Of Bacterial Pathogensmentioning
confidence: 61%
See 1 more Smart Citation
“…The four resistance genes investigated in this study have been reported among the most frequently detected resistance genes in soil [20,34]. Although we did not detect the existence of antibiotics in the soil, we identified ARGs conferring resistance to tetracycline and sulfonamide (tetW and tetM, and sulI and sulII, respectively).…”
Section: Discussionmentioning
confidence: 66%
“…[2][3][4] Recently, the detection of TC in aquatic environments has raised concern about its potential to promote the development of antibiotic resistance genes and pose a risk to humans. [5][6][7][8] As shown in Fig. S1, † TC possesses tricarbonylamide, phenolic diketone, and dimethylamine groups, which cause complexity in its behavior in aquatic media.…”
Section: Introductionmentioning
confidence: 99%